EFFORTS TO PREVENT STUNTING SINCE PREGNANCY WITH GETOL BAWEL IN THE WORKING AREA OF THE VILLA PERTIWI HEALTH CENTER, IN DEPOK - Siauta, Jenny Anna; Pangastuti, Apriliyati; Zebua, Arwani; Maharani P K, Aprinda; Nurullita, Claudia Ratih; Ratu, Elisabeth Mani; Martriyani, Nova; Fitriani, Nyi Imas (International Journal of Engagement and Empowerment (IJE2), 2024)
The prevalence of stunting in Depok City is 3,283 (3.24%) children who are stunted in a preliminary survey conducted randomly to pregnant women in the TPMB Bdn. Dian K area, it was found that some pregnant women still do not know about the prevention of stunting in children during pregnancy.   unting is the failure to grow or the abnormality of a child, which is usually characterized by weight or height that is not appropriate for his age, according to age less than -2 standard deviations (SD) in the World Health Organization (WHO) growth curve which occurs due to irreversible conditions due to inadequate nutritional intake and recurrent/chronic infections that happen in the first 1000 days of life (HPK). The government has tried to handle stunting by providing additional food to pregnant women and toddlers using local ingredients to make it accessible to the community. The provision of PMT gives good results. Namely, there is a decrease in the incidence of stunting every year. The purpose of this community outreach is to provide education and increase the knowledge of pregnant women about stunting prevention starting from the period of pregnancy, commonly known as the First 1000 Days of Life. The participants in this activity were 17 pregnant women and Posyandu Cadres. This activity began with a preliminary survey and a Forum Discussion Group (FGD) to determine problem priorities and carry out interventions. The intervention was carried out by providing counselling and pretests and posts to measure the success of counselling. Based on the results of the pretest, an average score of 86 was obtained, and the average score of the post-test was 100, which showed that the majority of participants experienced an increase in knowledge after providing education about stunting prevention. The advice given is that pregnant women always strive to fulfil nutritional needs, especially in 1000 HPK, by consuming nutritious foods such as GETOL BAWEL (Nuget, Tofu, Eggs, Leeks and Carrots).